Development of Multiple Input Battery Charger for Electric Bicycle Application - Yeak, Zu Yuan; Ahmad, Md Zarafi (Evolution in Electrical and Electronic Engineering, 2024)
The multiple input battery charger for electric bicycle applications represents a significant advancement in energy storage technology. This innovative charger is designed to accommodate various power sources, including solar, and conventional AC power (utility), enhancing the versatility and convenience of electric bicycles. By optimizing efficiency and maintaining battery health, it ensures longer operational lifespans. Its flexibility makes it suitable for diverse charging scenarios, from urban environments to remote and off-grid locations. Efficiently managing and prioritizing different energy inputs, the charger supports the use of renewable energy and improves energy security and sustainability. This technology allows electric bicycle users to charge their batteries from multiple sources, ensuring that they can keep their bicycles powered regardless of their location. In urban areas, users can easily switch between grid power and renewable sources like solar panels. As the demand for eco-friendly transportation increases, this multiple input battery charger is poised to play a vital role in promoting the widespread adoption of electric bicycles. It contributes to reduce carbon emissions and advances sustainable urban mobility solutions, making it a key component in the evolution of electric bicycle technology and fostering energy independence and resilience in the face of environmental challenges.